Strategi Komunikasi Pelayanan Pegawai MS Glow Tangah Jua Terhadap Pembeli Ditinjau Dari Perspektif Public Relation - Rena Dinata; Darul Ilmi (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
The development of the beauty business is currently very rapid in indoesia. In the service sector, it is an important part of a beauty company as a means of communicaton for companiens whose target is consumers. As time goes by, cosmetics are needed by all groups. This is one of the things that makes researchers interested in analyzing what kind of employee service communication strategies are used by employees of Ms Glow Tangah Jua Bukittinngi whether they are appropriate and relevant to the Public Relations perspective. This study aims to determine the employee service communication strategy carried out by Ms Glow Tangah Jua Bukittinggi from a Public Relations perspective. This research uses a descriptive method with a qualitative approach. The subject of this research is the employee and owner of Ms Glow Tangah Jua Bukittinggi and the object is the employee service communication strategy of Ms Glow Tangah Jua Bukittinggi in terms of Public Relations perspective. Meanwhile, in collecting data in this study, researchers collected data from observatio, interview and documentation. Based on the results of research with Ms Glow Tangah Jua Bukittinggi, a communication startegy that is appropriate and relevant to public relation is by greeting consumers well and greeting them when consumers arrive, the second strategy is educating consumers about the problems that occur on their skin, so that Ms Glow can handle and provide products that are suitable for consumers’ own skin problems.